Polymorphism of MDM2 promoter 309 (rs 2279744) and the risk of PCOS. (1st February 2016) - Chan, Ying; Jiang, Hongguo; Yang, Xiaoling; Li, Dongya; Ma, Lan; Luo, Ying; Tang, Wenru
Abstract: This study aimed at evaluating possible association between MDM2 SNP309 polymorphism (rs 2279744) and polycystic ovary syndrome (PCOS). One hundred and twenty-five women with PCOS and two hundred and fifty women without PCOS were collected from the department of reproductive medicine of college hospital in this case–control study. Peripheral blood samples were collected from all participants and DNA was extracted, MDM2 SNP309 polymorphism (rs 2279744) was determined from the 125 cases and 250 controls. Women were grouped into PCOS ( n = 125) group and control group ( n = 250). Odds ratios (OR) and 95% confidence intervals (CI) were used to evaluate the association between MDM2 SNP309 polymorphism (rs 2279744) and PCOS. The distribution of T allele was significant higher in PCOS cases than controls. MDM2 SNP 309 T allele is associated with PCOS.